2013
DOI: 10.4236/abcr.2013.21.001
|View full text |Cite
|
Sign up to set email alerts
|

Axillary “Exclusion”—A Successful Technique for Reducing Seroma Formation after Mastectomy and Axillary Dissection

Abstract: Introduction: A seroma is the commonest complication of breast cancer surgery, and although its consequences most often cause no more than discomfort and anxiety, more important sequelae include flap necrosis and wound breakdown. Infection developing within seroma increases morbidity and often results in the need for re-admission, re-imaging, drainage and antibiotic usage. Numerous methods to reduce post-mastectomy seroma formation have been tried with no consistent success. Methods: 24 consecutive patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The incidence of seroma formation in the study group (2%) was significantly less than that in group 2 (14%). Also in the same way with us Chand N, et al at (2012) [22] in their study on a small group (24 patients) found significant reduction (p < 0.01) of drainage volumes and incidence of seroma in the group they had closed off the axillary space from the remainder of the mastectomy cavity they reported an incidence of seroma (62.5%). 90% was in the control group and 42.5% in the study group with a reduction of about 65%.…”
Section: Discussionsupporting
confidence: 68%
“…The incidence of seroma formation in the study group (2%) was significantly less than that in group 2 (14%). Also in the same way with us Chand N, et al at (2012) [22] in their study on a small group (24 patients) found significant reduction (p < 0.01) of drainage volumes and incidence of seroma in the group they had closed off the axillary space from the remainder of the mastectomy cavity they reported an incidence of seroma (62.5%). 90% was in the control group and 42.5% in the study group with a reduction of about 65%.…”
Section: Discussionsupporting
confidence: 68%
“…None however have been found to be consistently successful, and consequently, none are used in the common practice. If it is believed that the lymphatics disruption in the axillary fossa are main aetiology, it follows that obliterating this space will minimize fluid collection [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seroma is graded 1 if asymptomatic (only diagnosed by ultrasound), graded 2 if symptomatic but can be managed either medically or by simple aspiration, and graded 3 if symptomatic and requires surgical or radiologic intervention [ 1 ]. The incidence of seroma following mastectomy and axillary clearance varies in reports from 25% to 60% [ 6 ], with even higher incidences being reported [ 1 ]. Despite the extensive investigation [ 7 15 ], the exact pathogenesis of postmastectomy seroma is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%